1986
DOI: 10.1073/pnas.83.15.5678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cDNA clones encoding the entire B-26 region of human apolipoprotein B.

Abstract: We report the characterization of intestine and liver cDNA clones for human apolipoprotein B (apoB) that map to the 5' end of the mRNA. The protein sequence encoded by the 5011 nucleotides derived from sequence analysis of these clones includes 1643 amino acid residues of the mature protein ofMr 184,000. The amino acid sequence at the amino terminus of B-74 peptide was determined and mapped to residue 1298. The size (Mr 145,700) and amino acid composition of the B-26 region encoded by these clones (including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In summary, the five epitopes that have been mapped to T4 on the Nterminal end of apo B are expressed on soluble apo B and do not require apo B association with lipids. This may indicate that apo B conformation in this region of the molecule, which is common to B-100 and B-48, is more affected by intrachain bonding, probably including disulfide bridges, consistent with the locally high number of cysteines in T4, 21 than by protein-lipid interaction.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In summary, the five epitopes that have been mapped to T4 on the Nterminal end of apo B are expressed on soluble apo B and do not require apo B association with lipids. This may indicate that apo B conformation in this region of the molecule, which is common to B-100 and B-48, is more affected by intrachain bonding, probably including disulfide bridges, consistent with the locally high number of cysteines in T4, 21 than by protein-lipid interaction.…”
Section: Discussionmentioning
confidence: 88%
“…The synthesis of peptides reproducing selected partial sequences of apo B on the T4 fragments 21 has allowed the production of specific antisera to these peptides; these antisera have been used in the further mapping of the epitopes present on T4. Monoclonal antibodies 9, 13, and 17 have been shown to compete with one another and with 1D1 in competitive binding experiments.…”
Section: Mapping Of Determinants Located Toward the N-termlnal Thrombmentioning
confidence: 99%
“…Protter et al (1986) suggested that residues 14-24 (Lys-Asp-Ala-Thr-Arg-Phe-Lys-His-Leu-Arg-Lys) of the amino-terminal end of apoB-100 might be a heparin-binding region. Although we did not isolate this peptide, we have found (unpublished results) that fragment T4 (in addition to T2 and T3) binds 125I-HRH on ligand blots, indicating one or more heparin-binding domains in the amino-terminal B-26 fragment of apoB-100 (Cardin et al, 1984c(Cardin et al, , 1986bProtter et al, 1986;Hardman et al, 1986).…”
Section: Discussionmentioning
confidence: 89%
“…1 illustrates the positions at which differences in the apoB-100 sequence have been reported. This information was assembled from known DNA polymorphisms (10,11) together with four complete cDNA sequences (12-15), a gene sequence (10), and several partial sequences (16,17). All reported variations are included, even though some may have resulted from cloning or sequencing errors.…”
Section: Resultsmentioning
confidence: 99%